2017
DOI: 10.1111/all.13306
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of allergy diagnosis and the potential impact of regulation in Europe

Abstract: In the European Union (EU), the regulatory framework regarding diagnostic allergen extracts is currently in the process of being implemented at the national level. Due to these regulations, the initial and periodic renewal expenses for the registration of diagnostic allergen extracts may render extract production unprofitable. Consequently, many extracts may be at risk of removal from the market. The current survey, which was conducted by a task force of the European Academy of Allergy and Clinical Immunology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 9 publications
(11 reference statements)
0
28
0
Order By: Relevance
“…In a recent survey of EAACI, the National Allergy Societies of Europe declared the lack of DAs a serious threat to current clinical practice. 9 Skin tests were shown to be the mainstay diagnostic procedure for the majority of allergic diseases and are used as first approach in 90% of patients with suspected inhalant allergies (asthma and rhinitis): organ-specific allergen challenges are regarded to be an important part of the diagnostic work-up. 9 The below listed recommendations given by this EAACI task force would facilitate better diagnosis and management of allergic diseases in European citizens.…”
Section: Discussion Of the E A Aci Ta S K Force Memb Er Smentioning
confidence: 99%
“…In a recent survey of EAACI, the National Allergy Societies of Europe declared the lack of DAs a serious threat to current clinical practice. 9 Skin tests were shown to be the mainstay diagnostic procedure for the majority of allergic diseases and are used as first approach in 90% of patients with suspected inhalant allergies (asthma and rhinitis): organ-specific allergen challenges are regarded to be an important part of the diagnostic work-up. 9 The below listed recommendations given by this EAACI task force would facilitate better diagnosis and management of allergic diseases in European citizens.…”
Section: Discussion Of the E A Aci Ta S K Force Memb Er Smentioning
confidence: 99%
“…In patients with upper airway allergies, skin tests such as SPT and intracutaneous tests (ICT) are the most commonly used in vivo methods to diagnose IgE-mediated allergic reactions (72)(73)(74)(75)(76) . A recent EAACI task force survey investigating the current practice of allergy diagnosis in Europe found that in almost twothirds of all types of allergic diseases and in 90% of respiratory allergies the diagnosis relies on skin tests as the first option (77) .…”
Section: Skin Testsmentioning
confidence: 99%
“…This was made possible by surveying all affiliated national societies inside and outside the EU. In total, 31 countries responded . The national societies were questioned about the types of tests used by their members and their awareness of national legislation pertaining to in vivo diagnostic tests and changes that might occur as a result of the transposition of Directive 2001/83 EC .…”
Section: The Future Of Diagnostic Allergens For In Vivo Testingmentioning
confidence: 99%